Metabolic enzyme-associated protein-protein interactions (mPPIs) in cancer: potential vulnerability for cancer treatment? - Tang Yu-ting; Chen Tian-yi; Liu Zi-yi; Luo Ming-yu; Gong Miao-miao; Shen Ying (Acta Pharmacologica Sinica, 2025)
Cancer metastasis and drug resistance are intricately linked processes that drive cancer progression and poor prognosis. One of the hallmarks of cancer is metabolic reprogramming, which evolves at various stages of tumor metastasis and drug resistance progression. This reprogramming involves the dysregulation of metabolic enzymes, which not only regulate the metabolic status in cancer cells, but also play multifunctional roles through influencing downstream signaling networks, acting as protein kinases, post-translational modifications and multiple biological processes, thereby exacerbating cancer malignancy. This review focuses on the metabolic enzyme-associated protein-protein interactions (mPPIs) during tumor metastasis and therapeutic resistance, and discusses the roles of key enzymes in glycolysis, the serine synthesis pathway, the pentose phosphate pathway, the glucuronate pathway and the sorbitol pathway. Understanding the distinct multifunctionality of these metabolic enzymes is crucial for gaining valuable insights into cancer pathogenesis and identifying potential therapeutic vulnerability to combat metastatic progression and overcome therapy resistance.